Peningkatan Pengetahuan Masyarakat Tentang Pengelolaan dan Pemilahan Sampah di Kelurahan Karangjati Kecamatan Bargas Kabupaten Semarang - Fitri Suprapti; Erwin Sutantyo; Ari Ani Dyah Setyoningrum; Evi Sirait; Purwanto (Universitas Nusa Putra & Persatuan Insinyur Indonesia, 2023)
This article discusses the management of household waste disposal and segregation in Karangjati Village, Bergas District, Semarang Regency. The background of this activity is that most of the people in this village work as factory workers, and they still have limitations in terms of waste management. Through Community Service this time it is hoped to be able to provide solutions to the problems faced by residents in Karangjati Village. The method for implementing this activity consists of (1) preparation, (2) implementation, and (3) evaluation with participants. The activity begins with the delivery of material with lectures, discussions, questions and answers about waste management and demonstrations about handling household waste such as food scraps and leaves for composting. The results of this community service activity show that the participants who took part in the activity from the beginning to the end of the activity have succeeded in increasing their understanding of waste management. This is indicated by the seriousness of the activity participants when doing waste sorting and composting practices.